Interpersonal Skills with a Focus on Creativity in Attention Deficit Hyperactivity Disorder - Kalogeratos, Gerasimos; Anastasopoulou, Eleni; Tsagri, Angeliki; Tseremegklis, Chrysostomos; Asimakopoulou, Sofia (Technium Social Sciences Journal, 2023)
Attention Deficit Hyperactivity Disorder (ADHD) is a highly prevalent and extensively researched psychological disorder in the field of child psychology. Nevertheless, numerous misconceptions have arisen despite the extensive research on this disorder. Specifically, certain studies have indicated that children with ADHD exhibit exceptionally elevated creative capacities. However, until recently, the empirical evidence to substantiate this assertion was incomplete. Most of the literature on this subject is primarily theoretical. It primarily centers around describing individuals who possess creative abilities, discussing the potential overlap between ADHD and creativity, and advising against the misdiagnosis of these conditions. This paper presents a comprehensive examination of the subclinical symptoms of ADHD and their correlation with creativity based on recent research.